Launching video for IIUM Special Plate Number - Mohamed Osman, Mariana; Shuid, Syafiee; Rabe, Noor Suzilawati; Muhamad Yusop, Siti Wahidah; Che Mohd Hashim, Ahmad Kamil; Hasbullah, Hafizah (2021)
This launching video is made in order to draw the attention of potential customers to the IIUM Special Plate Number. This video content of 1 minute contains facts and a convincing call-to-action for the bidding process in IIUM Special Plate Number